580 High dose-rate brachytherapy of localized prostate cancer converts tumors from cold to hot. (9th November 2020) - Keam, Simon; Halse, Heloise; Nguyen, ThuNgoc; Wang, Minyu; Losio, Nicolas Van Kooten; Mitchell, Catherine; Caramia, Franco; Byrne, David; Haupt, Sue; Ryland, Georgina; Darcy, Phillip; Sandhu, Shahneen; et al.
Abstract : Background: Prostate cancer is frequently cured with high dose-rate brachytherapy (HDRBT) radiation as a front-line treatment. Although considered to be an immune-excluded tissue, immune responses to radiation are implicated in driving tumour-eradication in prostate cancer. 1 This has not been proven, and yet is used as the rationale for clinical trials combining radiation and immunotherapies. 2 We hypothesise that there is a predictable relationship between radiation and the immune responses in prostate cancer that could be used to provide sound rationale for specific immune interventions in solid tumours that are made possible by radiation therapy. Methods: We present here new results stemming from our recently published immunoprofiling study of world-unique pre- and post-radiation tissues from 24 prostate cancer patients (figure 1A), RadBank cohort). 3 These samples were assessed using immune cell multiplex IHC, gene expression profiling, digital spatial profiling (DSP) and computational analysis of cell distribution. Results: This study unequivocally revealed that high dose-rate radiation converts predominately 'cold' prostate tumour tissue to a more activated 'hot' state comprised of two sub-types (high and a less activated intermediate state). These changes were evident in increased tumour inflammation gene signatures and immune checkpoint expression, immune cell composition changes, and alterations in spatial interactions. However, as 20% of the patients did not respond, we also explored pre-treatment gene signatures of patient responses to radiation – identifying potential mechanisms that prime tissues to respond more favourably. Most recently, we have explored three other important facets of the immune response to HDRBT: (i) putative differential drivers of high and intermediate responses (figure 1B), (ii) TCR clonality changes (figure 1C), and (iii) the influence of clinical features (e.g. Gleason grade) and treatment (e.g. androgen deprivation) (figure 1D). Differential expression analysis has identified key molecules (e.g. CD40LG and Lck expression) which are associated with higher activation responses. TCR sequencing of pre- and post-HDRBT tissue and peripheral circulating cells is also suggestive of engagement of the adaptive immune system and the emergence of tumor-specific T cells. Finally, multivariate analysis has also revealed that higher grade tumours exhibit higher basal levels of activation and IC expression – making them less sensitive to immune activation by HDRBT. Conclusions: We have begun to resolve clear patient and clinical classifiers based on immune responses to radiation, and identified patient groups likely to benefit from immune therapy alongside radiation. Importantly, these classifications are associated with baseline gene expression profiles that may be used for pre-clinical stratification and more sophisticated treatment paradigms. Ethics Approval: All participants provided consent covering tissue research as part of a prospective tissue collection study for prostate radiobiology research, approved by the Human Research Ethics Committee at the Peter MacCallum Cancer Centre (PMCC; HREC approvals 10/68, 13/167, 18/204). Consent: Written informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journal. References: Dudzinski SO, et al., Combination immunotherapy and radiotherapy causes an abscopal treatment response in a mouse model of castration resistant prostate cancer. J Immunother Cancer 2019. 7(1): p. 218. Kwon E.D., et al., Ipilimumab versus placebo after radiotherapy in patients with metastatic castration-resistant prostate cancer that had progressed after docetaxel chemotherapy (CA184-043): a multicentre, randomised, double-blind, phase 3 trial. Lancet Oncol 2014;15(7): p. 700–12. Keam SP, et al., High dose-rate brachytherapy of localized prostate cancer converts tumors from cold to hot. J Immunother Cancer 2020;8(1).